Implementation of Augmented Reality in the Development of Bioentrepreneurship-Based LKPD for Visualization of Fungi Material in High School - Sahil, Jailan; Nur, Taslim D.; Ahmad, Hasnah; Madan, Arifin; Rasyid, Rusman (JINAV: Journal of Information and Visualization, 2024)
The digital era demands educational transformation with relevant learning methods to prepare students to face the world of work. This study developed a Student Activity Sheet (LKPD) based on bioentrepreneurship assisted by Augmented Reality (AR) on fungi material. The aim is to encourage students' creativity and innovation and improve the quality of learning. The research method uses the R&D model with the define, design and develop (3D) stages. This research was conducted in one of the high schools in Ternate City. The research subjects consisted of three expert validators and 15 class X IPA students. The results of the study showed that the LKPD developed was very valid and feasible to use, and effectively improved the quality of student learning on fungi material in high schools.